Study to Assess the Maternal Factors Influencing Undernutrition among 3 to 6 Year Old Children of Davangere City - Ranjitha A; Angadi, Navinkumar; Mahabalaraju, DK (National Journal of Community Medicine, 2016)
Background: Nutritional status of children is an important indicator of health. Sociocultural and obstetric factors play an important role in the causation of under nutrition. In depth understanding of these factors is extremely necessary to formulate effective intervention strategy. Objective: To assess maternal factors influencing undernutrition of 3-6 year old children of Davangere city. Materials and methods: Community based case control study with a pre tested semi structured questionnaire interviewed mothers of 310 children attending anganwadis of Davangere city. Results: 76% Children were of 3-4 years of age and 57% were females among undernourished.23.3% cases and 4.6% controls were born to mothers’ whose weight gain during pregnancy was < 10kgs. 70.6% cases, 83.2% controls were observed among mothers’ who practised </= 2 years of spacing. Conclusion: Majority were from low socio economic status background and born to mothers with less education, early marriage (< 18 years) ,lesser antenatal weight gain (< 10 kgs) and birth spacing with < 2 years between the children concluding them as the important maternal factors influencing undernutrition.